Female Cyborgs, Gender Performance, and Utopian Gaze in Alex Garland’s Ex Machina - Georgi, Sonja (Zagadnienia Rodzajów Literackich, 2020)
The cyborg as a metaphor for cultural encodings of the interaction between humans and technology has been an accepted trope since the publication of Donna Haraway’s “Cyborg Manifesto.” Alex Garland’s 2015 film Ex Machina shares many of its key themes and motifs with earlier science fiction films, from Fritz Lang’s Metropolis to Ridley Scott’s Blade Runner. A first viewing of the film thus suggests an interpretation that focuses on the film’s portrayal of its female cyborgs Ava and Kyoko as another version of the “pleasure model” in the mode of Lang’s Maria or Scott’s Pris. However, it is the tension between Ava’s intelligence and visual attractiveness and her performance of a female gender identity that invites a closer investigation of the film’s visual encoding of the female cyborg. As the film shifts its focus from the young male programmer Caleb and his encounter with his employer Nathan and the cyborg Ava to Ava’s self-portrait, this chapter will take a closer look at the embodiment of cyborg identity.